2005
DOI: 10.1016/j.jnoncrysol.2005.04.078
|View full text |Cite
|
Sign up to set email alerts
|

Multiple glass transitions in the plastic crystal phase of triphenylene derivatives

Abstract: The dynamics and phase behavior of the discotic liquid crystalline compound hexahexyloxytriphenylene (HAT6) and a derivative were studied by broad-band dielectric spectroscopy, differential scanning calorimetry, X-ray diffraction and optical microscopy. While the pristine compound HAT6 forms both a columnar mesophase (Col h ) and a plastic crystal phase, no liquid crystallinity was observed for the highly asymmetric compound HAT6-C 10 Br. This paper focuses on the dielectric relaxations in the plastic crystal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
46
1

Year Published

2007
2007
2014
2014

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(48 citation statements)
references
References 25 publications
1
46
1
Order By: Relevance
“…This result indicates that the dynamics of the side chains in the PnAALAs as in the other families represented in this figure, are independent of the main chain structure and conformation and of the existence of crystalline paraffin-like lamellae. Another example of this situation has been found by Yildirim et al [16] in discotic liquid crystals where a hindered glass transition of the alkyl chains constrained by the columnar discotic structure exists. The comparison of the variation of the T x for a PE , occurring in nanodomains with the values of the glass transition in semi-crystalline and amorphous PE, seems to point to the similarity between the confinements imposed either by the reduction of the alkyl nanodomains sizes or by the size of the amorphous regions in semi-crystalline PE.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…This result indicates that the dynamics of the side chains in the PnAALAs as in the other families represented in this figure, are independent of the main chain structure and conformation and of the existence of crystalline paraffin-like lamellae. Another example of this situation has been found by Yildirim et al [16] in discotic liquid crystals where a hindered glass transition of the alkyl chains constrained by the columnar discotic structure exists. The comparison of the variation of the T x for a PE , occurring in nanodomains with the values of the glass transition in semi-crystalline and amorphous PE, seems to point to the similarity between the confinements imposed either by the reduction of the alkyl nanodomains sizes or by the size of the amorphous regions in semi-crystalline PE.…”
Section: Discussionmentioning
confidence: 83%
“…In the discotic liquid crystals the existence of a second cooperative mobility attributed to intracolumnar fluctuations of rotational disorder has also been reported [16].…”
Section: Discussionmentioning
confidence: 86%
“…47 Coming from high to low temperature, the ␣ relaxation presents onsets at 253 and 248 K for PG2.5 and PG10, respectively. [49][50][51] Recently, using molecular dynamics simulations, Karatasos 52 studied the effects that strong connectivity constraints in AB 2 type dendritic macromolecules may impart on the mechanisms involved in the manifestation of polymer glass transition phenomena. 48 The symmetry of the ␣␥ relaxation resembles the facet of a secondary absorption, but its high activation energy combined with the decrease of the relaxation strength of the process with increasing temperature suggests that the absorption may be a high temperature ␣ relaxation.…”
Section: Discussionmentioning
confidence: 99%
“…Earlier efforts through NMR [6 -13], dielectric spectroscopy (DS) [11][12][13][14][15][16][17][18], neutron scattering [19,20], and computer simulations [20 -22] have shed light on the dynamics. The NMR studies identified (i) the main process as reflecting the axial motion of the discs around the columnar axis [6,11] and (ii) quasiperiodic regions of high and low packing density along the columns [8] as proposed by de Gennes [23].…”
mentioning
confidence: 99%